Tinjauan Yuridis Terhadap Pertanggung Jawaban Pidana Anak Pelaku Pencurian Dengan Pemberatan - Wasahua, Ahmat Nawawi (JURNAL PROPERTY RIGHTS, 2014)
This study aims at determining the criminal liability of theft done by children by weighting and the legal reasoning of judges in imposing juvenile criminal theft by weighting.This research was conducted in the District Court Kepanjen by conducting direct interviews with the judges who decided the case of theft by weighting performed by the children as well as taking a copy of the decision related to solving problems by weighting the crime of theft comited by children.In addition, the researcher also conducted a study of literature by means of reviewing books, literature and legislation related to problems that are discussed in the thesis of the researcher.The findings obtained from this study include: (1) Accountabillity of perpetrators of criminal child theft by weighting that is a violation of article 363,paragraph 1 (a) 3 and 5 of the criminal code (KUHp), In addition, criminal liability is imposed in a criminal act of theft by weighting performed by the defendant by not looking at the value at stake and the reason for committing a crime, but whether or not the defendant committed the crime of theft by weighting. (2) Consideration of the judge in imposing criminal laws against child criminal theft by weighting based on the evidance; that is, the testimony of witnesses and the testimony of the defendant together with the evidance submitted by the General Prosecutor and the facts revealed in the trial.In addition, the criminal sanctions given are not intended to distroy the future of a child who has committed the crime of theft by weighting. But rather to privide a deterrent effect so that the child does not repeat such actions and make the child better and beneficial to the country and nation.